Hamka dan Konstruksi Pemikiran Kebebasan Beragama di Indonesia - Ahmad Mustaniruddin; Wahyu Pebrian; Fransisko Chaniago (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2022)
The existence of a significant quantity gap between religious adherents in Indonesia has the potential to lead to violations of religious freedom. And addition with the application of the rules regarding the right to religious freedom in Indonesia, which are felt to be not optimal, it has led to various arguments by Indonesian experts and scholars in responding to this, including Hamka who also contributed to the construction of ideas about religious freedom in one of his monumental works, namely Tafsir al-Azhar. For this reason, the presence of this study aims to present the construction of Hamka's thoughts regarding the phenomenon of religious freedom that occurs in Indonesia. This study used literature (Library research) with a qualitative approach. The data analysis used in this research is content analysis. In qualitative research, especially in qualitative verification strategies, this data analysis technique is considered to be the most frequently used data analysis technique. This study found that Hamka in his position as a scholar as well as a writer and humanist accepted the concept of religious freedom, especially in Indonesia. This is evidenced by his rejection of the element of coercion in embracing a religion, especially if it has the potential to cause conflict and violence between religions because of the truth claims of each religion (Claim Truth). Because according to him, Islam never teaches violence and war. However, behind Hamka's acceptance of religious freedom, he also puts a limit on the matter, namely that it is not permissible to combine faith and shirk.